THE HIERARCHY OF CONSUMER RIGHTS IN THE EVENT OF A LACK OF CONFORMITY OF THE GOODS IN SLOVENIAN, CROATIAN, AND SERBIAN LAW - Dudaš, Atila; Jokanović, Ivan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
This paper aims to compare the remedies at the consumer’s disposal in the event of a lack of conformity of goods in Slovenian, Croatian, and Serbian law. The Slovenian and Croatian legislators have already transposed Directive (EU) 2019/771 in 2022 and 2021, respectively. On the other hand, the rules of the Serbian Consumer Protection Act are still based on Directive 1999/44/EC. This Directive, however, also shaped the Slovenian and Croatian legislation long before the latest amendments. For this reason, the paper also analyses the rules in Slovenian and Croatian law which were in force before the recent amendments. The principal aim of the authors is to determine the similarities, peculiarities, and differences between the three legal systems.At present, the common denominator of the examined laws is the existence of a hierarchy of consumer rights: repair and replacement are the primary, and appropriate price reduction and termination of the contract the secondary or subsidiary remedies. Before the amendments in 2022 and 2021, termination of contract was the sole subsidiary remedy in Slovenian and Croatian law. It may be inferred that the most important differences between the examined legal orders concern the possibility of the termination of the contract, since the Slovenian and Serbian legislators considerably facilitated it when the lack of conformity becomes evident shortly after the delivery of the goods. Conversely, in Croatian law the emergence of non-conformity in a short period after the delivery does not immediately prompt the termination of contract. Presently, only Croatian law obliges the consumer, except in specific cases, to fix an additional period of reasonable length in which the seller can still perform the contract before the consumer’s statement aimed at the termination of the contract gains legal effect.
Keywords: саобразност, Закон о заштити потрошача, права потрошача, хијерархија права потрошача, оправка, замена, одговарајуће умањење цене, раскид уговора